Implementasi Fatigue Risk Management System di Politeiknik Penerbangan Indonesia Curug - Rudy Rudy (Jurnal Ilmu Ekonomi dan Sosial (JIES), 2022)
The purpose of this research is to study the issues regarding human factors, particularly on how to manage human fatigue, which hopefully can provide positive recommendations for the institution. This research is expected to contribute to raising awareness related to safety culture development in PPI-Curug, which will hopefully bring positive influence to the teaching and learning process of the cadets, and later in their working field once they have finished their program. The result of the research recommended to PPI-Curug through AMO 145D-910 is to implement those FRMS concepts and standards, as PPI-Curug is considered to be a leading aviation college in Indonesia. Thus, it has to be one step ahead in introducing and even implementing a concept that the researcher believes should be implemented as a mandatory matter in the Safety Management System in almost Indonesia Aviation industry fields. Meneliti tentang salah satu isu Faktor Manusia yaitu tentang pengelolalaan kelelahan dan berharap dapat memberikan rekomendasi yang positif bagi institusi. Penelitian ini diharapkan dapat meningkatkan kesiagaan berkaitan dengan upaya pengembangan budaya keselamatan di kampus PPI-Curug yang diharapkan dapat memberi pengaruh positif  proses belajar-mengajar para taruna kemudian dilapangan kerja pada saat mereka telah menyelesaikan program pendidikannya. Hasil penelitian merekomendasikan agar PPI-Curug  melalui fasilitas yang dimiliki yaitu AMO 145D-910 untuk juga mengimplementasikan konsep dan standar FRMS dengan alasan bahwa sebagai perguruan tinggi penerbangan terkemuka di Indonesia perlu selangkah lebih maju kedepan untuk memperkenalkan bahkan mengimplementasikan konsep yang diyakini oleh peneliti akan ditetapkan sebagai sesuatu yang wajib sebagaimana SMS yang telah diwajibkan untuk sebagian besar bidang di industri penerbangan Indonesia.